ANALISIS GENDER TINDAK PELECEHAN SEKSUAL TERHADAP PEREMPUAN DI KA’BAH - Mutia Tanseba Andani; Fathimah Nadia Qurrota A’yun (Jurnal Studi Gender dan Anak, 2023)
Sexual harassment can happen anywhere even in sacred spaces. Incidents of sexual harassment experienced by Pilgrims for Hajj and Umrah during their worship are facts that surfaced and went viral on social media. This article aims to reveal the triggering factors for sexual violence and the impact experienced by victims. This study is based on online media reporting information sources with gender analysis. Data collection techniques use documents and archives without direct interviews, or primary data on reports of sexual harassment at the Kaaba in CNN and BBC Indonesia news. The results of the analysis show that sexual harassment when carrying out the rituals of the Hajj/Umrah pilgrimage can occur due to several things (1) the existence of superior gender, (2) the patriarchal system that is still attached, (3) regulations between male and female pilgrims that do not have barriers. The sexual harassment that occurred at the Kaaba left a deep psychological impact on the victims who felt insecure while praying. Keyword:Sexual Harassment, Sexual Harassment at The Kaaba, Gender, Sexual Violence Abstrak Pelecehan seksual dapat terjadi di mana saja bahkan terjadi di ruang sakral. Peristiwa pelecehan seksual yang dialami oleh Jamaah Haji dan Umrah saat melakukan ibadah, adalah fakta yang mengemuka dan menjadi viral di sosial media. Artikel ini bertujuan untuk mengungkap faktor pemicu kekerasan seksual dan dampak yang dialami korban. Kajian ini didasarkan pada sumber informasi pemberitaan media online dengan analisis gender. Teknik pengumpulan data menggunakan dokumen dan arsip tanpa wawancara langsung, atau data primer pemberitaan pelecehan seksual di Ka’bah dalam berita CNN dan BBC Indonesia. Hasil analisis menunjukkan bahwa pelecehan seksual saat melaksanakan ritual ibadah haji/umroh dapat terjadi karena adanya beberapa hal (1) adanya gender superior, (2) sistem patriarki yang masih melekat, (3) peraturan antara jamaah laki-laki dan perempuan yang tidak adanya pembatas. Pelecehan seksual yang terjadi di Ka’bah menyisakan dampak psikologis yang mendalam terhadap para korban yang merasa tidak aman saat beribadah. Kata Kunci: Pelecehan Seksual, Pelecehan Seksual Di Ka’bah, Gender, Kekerasan Seksual